Unsaturated Hydraulic Characteristics of Compacted Local Geo-Materials for use as Landfill Liners - A. Demdouma; M. K. Gueddoudaa; I. Gouala; H. Souli (Algerian Journal of Research and Technology (AJRT), 2020)
The important hydraulic properties of compacted soil-bentonite liners in semiarid areas are hydraulic conductivity (ksat < 10-9 m/s), soil-water characteristic curve (SWCC) and initial water content. This paper studies the valorization of local materials containing calcareous sand, tuff obtained from Laghouat region (in South Algeria), to associate with bentonite in order to improve their hydraulic characteristics for use as landfill liner material. Firstly, the 10% bentonite + 20% calcareous sand + % 70 tuff mixture was selected based on the minimum saturated hydraulic conductivity (ksat) by the oedometric test. The results show that the effect of the initial water content variation from 12.35% to 16.35% does not make a difference in the ksat values; values are between 10-8 m/s and 10-11 m/s. Next, the unsaturated hydraulic conductivity (Kw) study of the adequate mixture with different initial water content was measured with an original vapor equilibrium technique (VET) used for Sr < 30% (very high suction s > 3 MPa). The results showed that the unsaturated hydraulic conductivity increases with the degree of saturation and decreases with the suction. The results showed that the Kw varied between, 3 10-17 m/s and 4 10-15 m/s, for one period of 90 days. The effect of initial water content on the Ksat and Kw of this mixture is hardly apparent for the much less (Sr>80%, k=ksat) and very high of suction values, respectively. In conclusion, the selected 10% bentonite + 20% calcareous sand + % 70 tuff mixture satisfies the regulatory requirements and hence constitutes a good local material for engineered barriers.